2021
DOI: 10.1186/s40337-021-00383-y
|View full text |Cite
|
Sign up to set email alerts
|

The abrupt transition from face-to-face to online treatment for eating disorders: a pilot examination of patients’ perspectives during the COVID-19 lockdown

Abstract: Background Studies investigating patients’ perspectives towards an abrupt transition from face-to-face to online treatment in eating disorders (EDs) are scarce. The current study aimed to (1) conduct a preliminary assessment of patients’ perspectives regarding this transition, and (2) explore potential demographic, clinical, and treatment-related factors associated with these perspectives. Methods Sixty-three patients with EDs whose treatment was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 59 publications
(35 reference statements)
3
62
0
1
Order By: Relevance
“…The main COVID-19-induced treatment change was a reduced access to in-person treatment [ 26 •, 27 •, 41 , 42 , 45 ]. Schlegl et al [ 26 •] found that the rate of BN patients receiving face-to-face treatment decreased from 82 to 36% during the lockdown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main COVID-19-induced treatment change was a reduced access to in-person treatment [ 26 •, 27 •, 41 , 42 , 45 ]. Schlegl et al [ 26 •] found that the rate of BN patients receiving face-to-face treatment decreased from 82 to 36% during the lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…The parallel increase of online treatment was often perceived as characterized by impairment in the quality of the therapy [ 26 •, 27 •, 37 •, 38 •, 41 , 42 , 44 46 ]. In this line, Lewis et al [ 45 ] also reported that 54% of the ED sample would not recommend the online treatment and 68% would not choose to continue the online therapy. Positive predictors of a good perception of the online therapy were longer illness duration, higher COVID-19-related anxiety, and stronger therapeutic relationship [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings highlight that at least some patients and families found the online intervention acceptable, despite the unfamiliarity of this intervention and the many obstacles described in its implementation. In this respect it is of note that a recent Israeli study ( 64 ) found mixed views of patients with EDs treated in a mainstream secular ambulatory service regarding the transition from face to-face to online treatment during the COVID-19 pandemic. This, the majority (68%) of the patients stated that they would not choose to continue online therapy given the option.…”
Section: Discussionmentioning
confidence: 99%
“…For those individuals who were in psychotherapy, additional challenges emerged as therapy sessions could not continue in-person due to the social restrictions imposed by health authorities. Millions of in-person therapies transitioned to online therapy via videoconferencing at once, without much preparation or support [12]. With the ongoing pandemic and its ripple effects on individuals' lives, attending online psychotherapy may provide support for patients in managing the experienced COVID-related distress.…”
Section: Introductionmentioning
confidence: 99%